2006
DOI: 10.1257/jep.20.4.177
|View full text |Cite
|
Sign up to set email alerts
|

How Richard Nixon Pressured Arthur Burns: Evidence from the Nixon Tapes

Abstract: Evidence from the Nixon tapes, now available to researchers, shows that President Richard Nixon pressured the chairman of the Federal Reserve, Arthur Burns, to engage in expansionary monetary policies in the run-up to the 1972 election. This paper quotes the relevant conversations from the Nixon tapes. Questions remain as to whether Burns followed an expansionary policy in an already-inflationary environment out of conviction or because of political pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…Numerous studies have shown the presence of monetary PBCs in the United States (Grier 1987(Grier , 1989Williams 1990;Carlsen 1997;Abrams andIossifov 2006) andin Germany (Johnson andSiklos 1994;Vaubel 1997;Lohmann 1998b). How can the Federal Reserve Bank and the Bundesbank, reputed to be the two most independent central banks in the world generate a PBC?…”
Section: Constraints On Economic Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown the presence of monetary PBCs in the United States (Grier 1987(Grier , 1989Williams 1990;Carlsen 1997;Abrams andIossifov 2006) andin Germany (Johnson andSiklos 1994;Vaubel 1997;Lohmann 1998b). How can the Federal Reserve Bank and the Bundesbank, reputed to be the two most independent central banks in the world generate a PBC?…”
Section: Constraints On Economic Policymentioning
confidence: 99%
“…An answer lies in the distinction between "de jure" or "legal" independence, i.e., that warranted by the central bank status, and "de facto" or "actual" independence, i.e., that which can be derived from observation of the central bank behavior (see, in particular Cukierman 1992, on this distinction). The difference observed between these two types of independence could be the result of pressures directly exerted by the government (Abrams 2006;Abrams and Butkiewicz 2012), or indirectly through interventions in the media presenting the government's side (Havrilesky 1988;Froyen et al 1997;Maier et al 2002). Government can also control the independent central bank through appointments to the board: see Havrilesky and Schweitzer (1990), Gildea (1990) and Havrilesky and Gildea (1992) for the United States, and Sieg (1997) and Lohmann (1998b) for Germany.…”
Section: Constraints On Economic Policymentioning
confidence: 99%
“…The first three quarters thus would straddle presidential terms. 34 See, for example, Abrams (2006). The US economy did grow faster under Democratic Fed chairmen than under Republican chairs.…”
Section: F Monetary Policymentioning
confidence: 99%
“…Since the decision to tighten credit or allow inflation has a redistributive consequence for borrowers and lenders, politicians may "outsource" decisions such as these to agencies believed not to be accountable to them, to "pass the buck" in terms of perceived responsibility for politically unpopular choices. Third, given the secrecy of central bank actions and the absence of a need to provide public reasons for their actions, politicians may well believe that they can influence central bank decisions in ways that escape public scrutiny, with central bank authorities sensitive to the desires of their politicians who appointed them (Abrams and Iossifov, 2006;Abrams, 2006;.…”
Section: Put Itmentioning
confidence: 99%